Burden of kidney disease among patients with peritoneal dialysis versus conventional in-centre haemodialysis: A randomised, non-inferiority trial. Issue 3 (May 2022) - Fan, Li; Yang, Xiao; Chen, Qinkai; Zhang, Hao; Wang, Jianqin; Chen, Menghua; Peng, Hui; Ni, Zhaohui; Wan, Jianxin; Yang, Hongtao; Li, Yun; Wang, Li; et al.
Background: Little is known about the impact of haemodialysis (HD) and peritoneal dialysis (PD) on health-related quality of life (HRQoL). We compared HRQoL between conventional in-centre HD and home-based PD in 1082 newly diagnosed kidney failure patients. Methods: This was an open-label, randomised, non-inferiority trial of adult patients with a diagnosis of end-stage kidney disease (estimated glomerular filtration rate ≤ 15 mL/min/1.73 m 2 ) requiring maintenance dialysis from 36 sites in China randomised 1:1 to receive PD or conventional in-centre HD. The primary outcome was the 'Burden of Kidney Disease' assessed using the Kidney Disease Quality of Life-Short Form (KDQoL-SF) survey over 48 weeks and the main secondary outcomes were the remaining scales of KDQoL-SF and all-cause mortality. The effect of PD versus HD on the primary outcome was compared by their geometric mean (GM) ratio, and non-inferiority was defined by the lower bound of a one-sided 95% confidence interval (CI) >0.9. Results: A total of 725 subjects completed the trial per protocol (395 PD and 330 HD, mean age 49.8 (standard deviation (SD) 14.4) years, 41.4% women). For the primary outcome, the mean (SD) change in 'Burden of Kidney Disease' over 48 weeks was 2.61 (1.27) in PD group and 2.58 (1.35) in HD group, and the GM ratio (95% CI) was 1.059 (0.908–1.234), exceeding the limit for non-inferiority. For the secondary outcomes, the PD and HD groups were similar in all scales. There were 17 and 31 deaths in PD and HD groups, respectively. Patients receiving PD had more adverse events, adverse event leading to hospitalisation and serious adverse events compared to those allocated to HD, but adverse events leading to death and discontinuation of the trial were not different between PD and HD. Conclusions: In this trial, PD may be non-inferior to HD on the 'Burden of Kidney Disease' among Chinese kidney failure patients who are of younger age and have lower comorbidity after 48 weeks' follow-up. Graphical Abstract This is a visual representation of the abstract.